Oxidative dehydrogenation of ethane to ethylene in a membrane reactor: A theoretical study - Rodriguez, Maria Laura (2010)
This contribution presents a theoretical study of a multitubular packed-bed membrane reactor for the ethane to ethylene oxidative dehydrogenation reaction over a highly active and selective Ni-Nb-O mixed oxide catalyst. This theoretical study takes into account the radial composition and temperature profiles using a two-dimensional pseudo-homogeneous model on the reaction side. The feasibility and convenience of using this novel design, as well as the influence of the main operating variables on the reactor performance, are analyzed. The introduction of the membrane leads to lower oxygen partial pressures inside the catalyst tubes, which results in an improved selectivity to ethylene (lower heat generation rates) and high effective heat transfer area per unit volume. The multitubular membrane reactor enables significant ethylene productions per tube and milder temperature profiles than a conventional wall-cooled fixed-bed reactor. Operating conditions have to be carefully adjusted to avoid undesired oxygen accumulation inside the tubes. The presence of small amounts of oxygen at the reactor inlet significantly improves the ethylene production rates. © 2010 Elsevier B.V. All rights reserved.